A halogen-bonding foldamer molecular film for selective reagentless anion sensing in water. Issue 33 (5th April 2019) - Hein, Robert; Borissov, Arseni; Smith, Martin D.; Beer, Paul D.; Davis, Jason J.
Abstract : A novel halogen-bonding foldamer molecular film was utilised to achieve anion sensing in pure water via non-faradaic capacitance spectroscopy. Abstract : We describe self-assembled monolayers of novel halogen-bonding and hydrogen-bonding foldamer receptors capable of selectively recruiting perrhenate, iodide and thiocyanate in water. Unprecedented anion sensing via impedance-derived capacitance spectroscopy enables subsequent sensitive and selective anion detection without the need for a redox probe. Importantly, the sensing of any anion should be possible using this novel electrochemical approach.